Formulation and Evaluation of Microsphere of Oxalis Stricta Extracts and Its Anti-Microbial Activity - Raghvendra Kumar Mishra, Ashish Jain, Mahadev Kanere, Akhlesh Kumar Singhai (Journal of Neonatal Surgery, 2025)
Objective: The purpose of the present investigation was to Formulate and evaluate microsphere of Oxalis stricta extract and its anti-microbial activity Methods: The extract-loaded microspheres using biological macromolecule ethyl cellulose (EC) was prepared by solvent evaporation method using HPMC polymer. The effects of different process and formulation variables (stirring speed, evaporation time, and drug/polymer ratio) on microsphere properties were investigated. Results: SEM revealed the spherical nature of the produced microspheres. Particle size study revealed that the average particle size of microspheres ranges from 798.9 to 959.3 nm. These particle size values indicate that the all formulated microsphere is under the range of microsphere and F2 is the lowest particle size of all formulation and Zeta potential was found to be all formulation range -1.7 to -4.1 mV with peak area of100% intensity. The formulation remained physically and chemically stable for three months under accelerated stability conditions (250C±2 0C and 60 ± 5% RH) and (400C±2 0C and 70 ± 5% RH). Conclusion: The current study's findings indicate that microsphere formulations are a promising carrier for new herbal medication delivery.